Review of the Supervision of the DPRD's Funtion in the Management of the APBD to Achieve Good Governance in Gorontalo Province - Arni Junita Hamisi hamisi; Arifin Tahir; Arfan Arsyad (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This study aims to determine the supervisory function of DPRD in APBD management in order to realize good governance in Gorontalo Province and to determine the factors that hinder DPRD's supervisory function in APBD management in order to realize good governance in Gorontalo Province.. This type of research is descriptive qualitative. In this study there are two sources of data, namely primary data sources and secondary data sources. The data collection techniques used in this study were interviews, observation, and documentation studies. The data analysis techniques in this study are: data reduction, data presentation, conclusions and data verification. The results of the research show that the DPRD's supervisory function in managing the APBD in order to realize good governance in Gorontalo province has been running as it should. Aspects of the DPRD's supervisory function in the management of the APBD have been running quite well, it can be seen from: (1) Supervision Standards, in general the DPRD's supervisory function has been carried out. Although repressive supervision has not really been implemented. (2) Evaluation of Supervision Results has been carried out in accordance with the basis of supervision and control. The DPRD's efforts in carrying out the evaluation of the monitoring results can be seen from several policy decisions which after being criticized have resulted in policy changes. (3) Information Disclosure has been carried out by the Gorontalo Provincial DPRD, although publication efforts as a form of implementing the provisions of the law in which public information must be easily accessible by the public has not been confirmed by the DPRD